Universality or contingency of the transnational model : the lessons of the Catholic University of West Africa case - (:unkn) unknown (My University, 2014)
Presented as an organization model to face globalization in the early 90’s by Bartlett & Ghoshal, The transnational has inspired lot of researchers.The problematic of this thesis aims to verify whether the transnational structure is an organization which fits firms only.With the help of a case study applied to a network structure “The catholic University of West Africa” and based on existing Theories in management and multinational governance, our work will attempt to test this hypothesis in an experimental research field in an African Context. This field is illustrated by a non-profit religious organization.The results allowed us to realize that the transnational model can be implemented in this kind of organization, but one should proceed step by step to achieve a global integration of all the operational and functional activities, starting by those alleged to be more relevant. The impact of religion and non-profit organization has been highlighted as factors playing a positive role in the studied cases.
Keywords: African Research